Myocardial fibrosis rather than hypertrophy induces diastolic dysfunction in renovascular hypertensive rats - Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Okoshi, Marina Politi [UNESP]; Franco, Marcello; Cicogna, Antonio Carlos [UNESP] (Canadian Science Publishing, 1997)
The aim of the present study was to evaluate the effect of interstitial fibrosis alone or associated with hypertrophy on diastolic myocardial function in renovascular hypertensive rats. Myocardial function was evaluated in isolated papillary muscle from renovascular hypertensive Wistar rats (RHT, n = 14), renovascular hypertensive rats treated with the angiotensin converting enzyme inhibitor (ACEI) ramipril, 20 mg · kg-1 · day-1 (RHT RAM, n = 14), and age-matched unoperated and untreated Wistar rats (CONT, n = 12). The ACEI treatment for 3 weeks allowed the regression of myocyte mass and the maintenance of interstitial fibrosis. Myocardial passive stiffness was analyzed by the resting tension - length relationship. The myocardial fibrosis was evaluated by measuring myocardial hydroxyproline (Hyp) concentration and by histological studies of the myocardium stained with hematoxylin and eosin or picrosirius red. Left ventricular weight was significantly higher in RHT (0.97 ± 0.12 g) compared with CONT (0.66 ± 0.06 g) and RHT RAM (0.69 ± 0.14 g). The Hyp levels were 2.9 ± 0.4, 3.4 ± 0.3, and 3.8 ± 0.4 μg/mg of dry tissue for the CONT, RHT, and RHT RAM, respectively. Perivascular and interstitial fibrosis were observed in RHT and RHT RAM groups. There were lymphomononuclear inflammatory exudate and edema around arteries, involving adjacent myocytes in the RHT group. There was an increased passive stiffness in RHT and RHT RAM groups compared with the CONT group. In conclusion, our results indicate that the impaired diastolic function in the renovascular hypertensive rats is related to interstitial fibrosis rather than to myocardial hypertrophy.
Keywords: Angiotensin converting enzyme inhibitor; Collagen; Papillary muscle; Passive stiffness; Renovascular hypertension